Review: Current status of ethnobiological studies in Merauke, Papua, Indonesia: A perspective of biological-cultural diversity conservation - MAIKEL SIMBIAK; JATNA SUPRIATNA; NISYAWATI; EKO BAROTO WALUJO (Society for Indonesian Biodiversity, 2019)
Abstract. Simbiak M, Supriatna J, Walujo EB, Nisyawati. 2019. Review: Current status of ethnobiological studies in Merauke, Papua, Indonesia: A perspective of biological-cultural diversity conservation. Biodiversitas 20: 3455-3466. Ethnobiology is a scientific study that examines the dynamic relationship between humans, biota and the environment. In this dynamic relationship, holistic notions that integrate humans and their cultural and biological diversity give more responsibility to ethnobiological studies. This research approach stimulates insights to integrate scientific research with awareness of political and ecological issues, loss of biological resources, including indigenous peoples' struggles over land and resources, identity degradation due to loss of culture and language. Ethnobiological studies undertaken in Merauke, Papua between 2000 and 2017 were reviewed from the perspective of biological-cultural diversity conservation. The aims and results of such published ethnobiological studies were analyzed and we found the failure of such studies in accounting for linguistic diversity in the region while documenting ethnobiological knowledge. Most of such ethnobiological studies were oriented on the topic of economic botany, focusing on recording the potential uses of plants utilized by each ethnic group in the Marind language-culture area of Merauke District, especially those belonging to the domain of medicinal plants. Some studies also used artificial community terminology to treat several ethnic groups as uniform and did not mention what language used for the local names of plants in their reports. Future ethnobiological research in the area would benefit from: (i) adopting a cognitive ethnobiology orientation; (ii) applying appropriate ethnolinguistics standards of research to document the languages; and (iii) using a quantitative approach to analyze the distribution of ethnobiological knowledge within the communities studied. The latter approach is especially important given the extreme and rapid changes of the environment in this region.